Document AI: Benchmarks, Models and Applications (In Chinese) - Cui, Lei; Xu, Yiheng; Lv, Tengchao; Wei, Furu (CCL 2021, 2021)
Document AI, or Document Intelligence, is a relatively new research topic that refers to the techniques to automatically read, understand and analyze business documents. It is an important research direction for the interdisciplinary of natural language processing and computer vision. In recent years, the popularity of deep learning technology has greatly advanced the development of Document AI tasks, such as document layout analysis, document information extraction, document visual question answering, and document image classification etc. This paper briefly introduces the early-stage heuristic rule-based document analysis, statistical machine learning based algorithms, as well as the deep learning based approaches especially the pre-training approaches. Finally, we also look into the future direction of Document AI.